Influence of toys on behavioural patterns of pigs and their association with the concentration of serotonin in blood plasma - Lykhach, A. V.; Lykhach, V. Y.; Shpetny, M. B.; Mykhalko, O. H.; Zhyzhka, S. V. (Regulatory Mechanisms in Biosystems, 2020)
Improvement of welfare of piglets is one of the key factors which underlie the effectiveness of producing pork and the profitability of pig farming. This article offers a solution to the main industrial problem – creation of comfortable maintenance conditions for pigs using toys which satisfy their ethological needs. Piglets used in the experiment were kept in the swine complex of agricultural production of Agrofirm Mig-Service-Agro Cooperative in Novoodesky district of Mykolaiv Oblast (Ukraine). The objective of the study was assessment of the effect of toys on the behaviour of piglets, level of concentration of hormone serotonin in blood plasma and their energy of growth. The experiment was performed on 120 weaned piglets aged 28 days, which were divided according to the principle of analogues with 60 individuals in each group: I – the control group, the animals were kept with no toys; II – the experimental group, where the animals had toys. During the experiment chronometric monitoring of the piglets’ behavioural acts was carried out using video observation, we extracted blood samples for determination of the content of the hormone serotonin using the method of highly-efficient fluid chromatography and assessed the growth of the piglets. After the end of the experiment, we determined that the presence of toys reduced the intragroup aggression, which was accompanied by decrease in the duration of fights and almost three-fold increase in playing behaviour. Among piglets which had access to toys, the number of individuals observed to bite tails and ears decreased from 11 to 3. In the period of the study, the concentration of serotonin in the blood plasma of piglets who had free access to toys was 10 times higher compared with animals of the control group. Change in the behaviour patterns among the animals of the experimental group led to significant differences regarding the parameters of growth, where probable increase in the live weight at the age of 90 days was observed, which was associated with significant increase in their mean daily weight gain compared with the animals of the control group. This study confirms that use of toys for piglets during growth completion can prevent features of aggression and abnormal forms of stereopathy within groups, increase the live weight and mean daily weight gain and improve emotional condition, which affects the welfare of pigs.